The impact of the Employment Equity Act on female inter-industry labour mobility and the gender wage gap in South Africa - Mattie Susan Landman; Neave O'Clery (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
The Employment Equity Act No. 55 of 1998 was introduced by the South African government to address the legacy of apartheid and ensure equitable representation of black people and women in the South African labour market. Although the impacts of the Act are highly controversial, its widespread adoption among firms opens up questions on its impact on the structure of the South African labour market. This study primarily focuses on determining the impact of the Act on female inter-industry labour mobility and the gender wage gap. Using a regression discontinuity design, we show that as a firm becomes compliant with the Act, this increases the diversity of sectors from which the firm hires new female workers (the female inflow diversity), and increases the firm's average female wage. We also find that the more male-dominant an industry is, the higher its female inflow diversity and the smaller its gender wage gap. This relationship is significantly stronger among the group of firms that comply with the Act compared to those that are exempt. These results suggest that firms that comply with the Act, and particularly those in male-dominant industries, have adopted the following two recruitment strategies in order to feminize their workforce: they have diversified recruitment to a larger number of sectors, and they have increased the average female wage.
Keywords: D04; J24; 330; Employment Equity Act; gender wage gap; industry networks; labour dynamics